(untitled) (Journal of Forestry, 2024)
Wild goat (Capra aegagrus Erxleben, 1777) is a prominent mountain mammal found in many habitats in Türkiye, but few studies have investigated its relationship with its habitat. This species is significantly affected by various anthropogenic activities such as illegal hunting and marble quarries. This study aimed to determine the changes in potential suitable habitats for wild goats over time by creating habitat suitability models. This study was carried out in the province of Isparta. The occurrence data of wild goats also were collected mostly from Sütçüler and Eğirdir districts. The data were obtained for two periods, 2009 and 2019. The habitat suitability modeling was performed using the Maximum Entropy (MaxEnt) method. The results showed that habitat use of wild goat was influenced by factors such as elevation, ruggedness, slope, radiation index, annual precipitation (bio12), and annual mean temperature (bio1). The AUC values for the training and test datasets of the model obtained using data from the year 2009 were found to be 0.990 and 0.987, respectively. Similarly, for the year 2019, the values were found to be 0.987 and 0.978, respectively. It was observed that the identified suitable areas for both periods were mostly limited to local areas in the southwest and southeast of the study area. Finally, the habitat suitability maps were thresholded at 0.5 value. As a result, the thresholded habitat suitability maps predict that there could be a 2,659-hectare (ha) increase in potential suitable areas in 2019.